The Effect of Audit Risk and Workload on Fraud Detection Through Auditor Professional Skepticism - Aldrin Akbar; Yana Ermawati; Suratini Suratini; Fahrudin Pasolo; Entar Sutisman (Atestasi : Jurnal Ilmiah Akuntansi, 2022)
This study examines and determines the effect of audit risk and workload on fraud detection through auditors' professional skepticism at the Papua Inspectorate. The population in this study were all 53 auditors at the Papua Inspectorate office. Sampling in this study was carried out using the census sampling method. Sources of data used are primary data collected by distributing questionnaires to all respondents. The statistical method used to test the hypothesis is to use multiple correlations with the help of SmartPLS software. Data analysis consists of descriptive statistical analysis, measurement model tests, outer models consisting of (convergent validity, discriminant validity, composite reliability) and structural model tests, or the inner model is evaluated using R-square for the dependent construct, direct and indirect hypothesis testing. The results showed that the audit risk variable had a positive and significant effect on fraud detection, the workload variable had a negative and significant impact on fraud detection, and the skepticism variable had a positive and significant effect on fraud detection. The audit risk variable positively and significantly impacts fraud detection through skepticism, and the workload variable negatively and significantly affects fraud detection through skepticism.